1977
DOI: 10.1192/bjp.131.5.448
|View full text |Cite
|
Sign up to set email alerts
|

Handedness in Psychiatric Patients

Abstract: Eight hundred psychiatric patients and eight hundred controls completed a handedness preference questionnaire. There was no significant difference in handedness between the two samples, but, contrary to some previous reports, excess of sinistrality was not associated with male sex. The distribution of handedness was similar in neurotics and controls, but among psychotics in general there was a higher proportion of fully right-handed subjects. Among schizophrenics there was a significantly higher proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Increased NRH in SZ seems established (Hirnstein and Hugdahl, 2014), but research on differences between BPD and both SZ and HC, and the specificity of differences to BPD with psychotic features, is limited. Studies comparing NRH between SZ and affective psychosis often combined patients with BPD and depression, (Fleminger et al, 1977; Malesu et al, 1996), whereas studies comparing NRH between SZ and BPD did not clearly differentiate between BPD with and without psychosis (Clementz et al, 1994; Yan et al, 1985). These studies yielded inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Increased NRH in SZ seems established (Hirnstein and Hugdahl, 2014), but research on differences between BPD and both SZ and HC, and the specificity of differences to BPD with psychotic features, is limited. Studies comparing NRH between SZ and affective psychosis often combined patients with BPD and depression, (Fleminger et al, 1977; Malesu et al, 1996), whereas studies comparing NRH between SZ and BPD did not clearly differentiate between BPD with and without psychosis (Clementz et al, 1994; Yan et al, 1985). These studies yielded inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…The overall effect of a pathological process affecting lateralization in a certain group of individuals would therefore be a shift away from dextrality to nonright-handedness. Several studies of handedness and schizophrenia using a dichotomous classification have found that schizophrenic patients have an increased rate of non-right-handedness (20%) compared with normal subjects [10][11][12][13][14] with two exceptions [15,16], who found an excess of dextrality. Using a broader category of 'nonright-handedness' in schizophrenia, different studies found an association between schizophrenia and non-right-handedness but no increase in pure left-handedness [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Examining sex differences in patients' motor asymmetries, together with reports of sex differences in similar types of measures in animals (Fleminger et al 1977;Robinson et al 1980;Brass and Glick 1981;Ross et al 1981;Manoach 1994), supports the view that gonadal hormones may play an important role in the prenatal development and adult expressions of lateralized motor functions in schizophrenia. As mentioned above, research in animals shows that motor asymmetries in males and females are differentially affected by exposure to a variety of factors during early development Camp et al 1984;Alonso et al 1991).…”
Section: Laterality In Animals and In Schizophrenia Patientsmentioning
confidence: 80%
“…Lateralized disturbances in patients with schizophrenia have been noted at many levels of behavioral analysis (Nasrallah 1986). Some early studies of anomalous laterality found disturbances in basic cognitive, perceptual, and motor behaviors (Flor-Henry 1976;Gur 1977Gur , 1978Gruzelier and Hammond 1979), in addition to evidence for abnormal distributions of hand preference in schizophrenia populations (Boklage 1977;Fleminger et al 1977). These studies laid the groundwork for exploration into the sensory (Carr et al 1992;Mathew et al 1993), motor (Bracha 1987Gorynia and Uebelhack 1992;Lohr and Caligiuri 1995;Sakuma et al 1996), attentional (Posner et al 1988;Tomer and Flor-Henry 1989;Harvey et al 1993;Carter et al 1994;Bustillo et al 1997;Evans and Schwartz 1997), and cognitive manifestations (Saykin et al 1991(Saykin et al , 1994Green et al 1994;Haut et al 1996;Sakuma et al 1996) of behavioral asymmetry that have continued to demonstrate striking differences between patients with schizophrenia and normal controls.…”
Section: Laterality In Animals and In Schizophrenia Patientsmentioning
confidence: 99%
See 1 more Smart Citation